Study of bacteria isolated from COVID-19 and non-COVID-19 intensive care units and determination of their antibiotic susceptibility profiles - Kilinç, Çetin; Coplu, Nilay; Yaşar Duman, Melike; Çalişir, Büşra; Tüfekci̇, Enis Fuat; Gülhan, Muhammet; Yilmaz, Ayşe; Soylu, Veysel Garani (Ondokuzmayis University, Faculty of Medicine, 2022)
Nosocomial infections are infections that occur 48-72 hours after hospitalization, especially caused by bacteria, and pose a high risk for patients in the intensive care units (ICUs), including Covid-ICU. This study was aimed to reveal the distribution and antibiotic susceptibility profiles of bacteria isolated from various clinical samples of non-Covid-ICU and Covid-ICU patients. Bacterial strains isolated from ICUs patients in Kastamonu Training and Research Hospital between March 2020 and October 2020 were included in this study. The identification of the strains was carried out using the Vitek 2 compact automated system (BioMerieux, France) as well as standard microbiological methods. Antibiotic susceptibility tests were studied using the Vitek 2 automated system and the results were interpreted based on the European Committee for Antimicrobial Susceptibility Tests (EUCAST) guideline. There were 302 patients in the non-Covid-ICU and 440 patients in the Covid-ICU. A total of 470 strains, 370 from non-Covid-ICU and 100 from Covid-ICU, were isolated. Acinetobacter spp was the most frequently isolated species for both ICUs. Acinetobacter spp isolated from non-Covid-ICU had higher resistance rates to meropenem (p= 0.043), ceftazidime (p= 0.014), and levofloxacin (p=
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi; Acinetobacter; antibiotic resistance; Covid-intensive care unit; nosocomial infections; 3. Good health